ZAKAT ACCOUNTING GUIDELINES BASED ON COMPARISON BETWEEN ZAKAT ACCOUNTING PSAK 109 AND FAS (9) AAOIFI - M. Sudirman; Muhammad Hasbi Zaenal; Sigid Eko Pramono (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2020)
This research will analyze the Sharia Accounting as specifically which deals with the Zakat based on comparative analysis of PSAK 109 with FAS (9) AAOIFI. The method that used in this research is qualitative research and comparative descriptive that is a method which describes, compares a data and a situation and explains a situation so that a conclusion can be drawn, with in-depth interviews.